PEMANFAATAN GETDIGEST UNTUK MEREVIEW ARTIKEL ILMIAH GUNA MENUNJANG PENYUSUNAN TUGAS AKHIR MAHASISWA - Suharli Suharli; Andi Haris; Supratman Supratman (FKIP Universitas Samawa, 2022)
The difficulties that students feel when starting to compose their final project are the biggest obstacles in completing their obligations. This has an impact on the length of their process in completing the study. The solution to this is to use Getdigest to review articles that will be used as references in the final project. The purpose of this activity is to assist students in reviewing scientific articles as a reference for their final project by using Getdigest. This activity was held by the Student Representative Council of the Faculty of Teacher Training and Education (FKIP) of Universitas Samawa as a form of their concern for the problems experienced by final semester students at FKIP. The lecture method is used to convey material during the activity. This activity received a positive response from students who have been having difficulty starting to prepare their final project.